Giant osteoblastoma of temporal bone: case report - FIGUEIREDO,EBERVAL GADELHA (1998)
Benign osteoblastoma is an uncommon bone tumor accounting for approximately 1% of all bone tumors. There are only 35 cases of skull osteoblastoma reported in the literature. We describe the case of a 23 year old male with a giant osteoblastoma of temporal bone submitted to a total removal of the tumor after an effective embolization of all external carotid branches. The authors discuss diagnostic and management aspects of this uncommon skull tumor.